Ambivalence of Disgust: Aurel Kolnai on the Significance of the Secondary Intention - Šinkūnas, Tomas (Problemos, 2022)
Today, scholars struggle to provide a coherent account of the unique, unitary structure of disgust as portrayed in Aurel Kolnai’s essay On Disgust. And even though Kolnai stressed that ambivalence was the main challenge in accounting for the essence the phenomenon, it had yet to receive its proper treatment by scholars. In this paper, I highlight the importance of the constitutive elements of disgust in establishing a structurally coherent, unitary, originary sense of the phenomenon. By highlighting and elucidating the connections between Kolnai’s account of ambivalence, double intention and life and death, I am able to evince several key misconceptions of his theory, and thereby comprehensively account for the unitary structure of disgust.
Keywords: disgust; ambivalence; Kolnai; life; death; secondary intention